In aid of świetliczarka (‘a day-care room supervisor’). On researching ‘badly represented’ lexis in Polish dictionaries - Duda, Henryk (Papers in Linguistics, 2021)
In Poland, in contemporary Polish ‘a supervisor, an employee of a day-care room, which is an educational institution’ is referred to as świetliczanka (a day-care supervisor). Nevertheless, a slightly different word describing the same profession (świetliczarka) is used by part of Polish emigrants based in various countries, including the United Kingdom and the United States of America. Employing Internet search engines, the author managed to demonstrate that the noun świetliczarka originated earlier than świetliczanka. However, analysis of applications of the doublet świetliczarka : świetliczanka allows one to presume that the former was eliminated from the Polish language used in Poland possibly due to extra-linguistic factors, as this noun was associated with both the reality of the Second Polish Republic and the Polish Armed Forces in the West. In the light of the conducted analysis, applying new methods of collecting lexical data seems to be extremely promising in linguistic research.